Semi-Automated Live Tracking of Microglial Activation in CX3CR1GFP Mice During Experimental Autoimmune Encephalomyelitis by Confocal Scanning Laser Ophthalmoscopy - Frenger, Moritz J.; Hecker, Christina; Sindi, Mustafa; Issberner, Andrea; Hartung, Hans-Peter; Meuth, Sven G.; Dietrich, Michael; Albrecht, Philipp (Frontiers in Immunology, 2021)
Confocal scanning laser ophthalmoscopy (cSLO) is a non-invasive technique for real-time imaging of the retina. We developed a step-by-step protocol for the semi-automatic evaluation of myeloid cells in cSLO images from CX3CR1-GFP mice, expressing green fluorescent protein (GFP) under control of the endogenous CX3C chemokine receptor 1 locus. We identified cSLO parameters allowing us to distinguish animals with experimental autoimmune encephalomyelitis (EAE) from sham-treated/naïve animals. Especially cell count (CC) and the total microglial area (SuA) turned out to be reliable parameters. Comparing the cSLO results with clinical parameters, we found significant correlations between the clinical EAE score and the SuA and of the inner retinal layer thickness, measured by optical coherence tomography, with the CC as well as the SuA. As a final step, we performed immunohistochemistry to confirm that the GFP-expressing cells visualized by the cSLO are Iba1 positive and validated the step-by-step protocol against manual counting. We present a semi-automatic step-by-step protocol with a balance between fast data evaluation and adequate accuracy, which is optimized by the option to manually adapt the contrast threshold. This protocol may be useful for numerous research questions on the role of microglial polarization in models of inflammatory and degenerating CNS diseases involving the retina.